Development of the Game "Construction Fitness Signs" to Stimulate Basic Locomotor Movement Skills in Early Childhood - Putri, Mu'Alfani Arsana; Pramono, Pramono; Maningtyas, Rosyi Damayani T. (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Early childhood education is a learning process carried out by facilitating the growth and development of children holistically and emphasizing all aspects of children's development achievements. The purpose of this research is to produce a game "Construction Fitness Signs" that stimulates basic locomotor movement skills including 6 elements of physical fitness in early childhood equipped with guidebooks and learning videos for users. This type of research is Research and Development (RnD) using the synthesized Borg and Gall model. The instrument analysis technique was obtained from quantitative data from the validation results of experts, namely motor physicists, learning experts, and game experts. The results of the validation of the motor physicist showed the ideal of 98.07%. Learning expert scores with 96.87% criteria, and game experts having 94.73% criteria are declared safe, interesting, and easy games to apply to early childhood. The use test and the application test were carried out obtained from the results of the small group test recapitulation, the test of the use of guidebooks and learning videos, the large group test, the effectiveness test, and the attractiveness test. Qualitative data from observations and interviews with 3 principals. The researchers found that the implementation of the "Construction Fitness Signs" game had 3 eligibility criteria, namely effective, efficient, and attractive for stimulating basic locomotor movement skills in early childhood learning activities. The use test and the application test were carried out obtained from the results of the small group test recapitulation, the test of the use of guidebooks and learning videos, the large group test, the effectiveness test, and the attractiveness test. Qualitative data from observations and interviews with 3 principals.